2017
DOI: 10.1089/neu.2015.4392
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Cortical Emotion Processing Circuits after Mild Traumatic Brain Injury from Motor Vehicle Collision

Abstract: Mild traumatic brain injury (mTBI) patients frequently experience emotion dysregulation symptoms, including post-traumatic stress. Although mTBI likely affects cortical activation and structure, resulting in cognitive symptoms after mTBI, early effects of mTBI on cortical emotion processing circuits have rarely been examined. To assess early mTBI effects on cortical functional and structural components of emotion processing, we assessed cortical activation to fearful faces within the first 2 weeks after motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…Some authors have found correlates between level of emotional distress after concussion and autonomic anomalies. It is unclear at this point to what extent the emotional impact of concussion reflects the physiologic impact of situational/physical/emotional stressors associated with the injury or direct physiologic impact of the injury to the emotional circuitry in the brain ( X. Wang et al, 2017 ). It is also unclear to what extent circuitry associated with resilience, such as pain resilience might also be compromised ( Leung et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have found correlates between level of emotional distress after concussion and autonomic anomalies. It is unclear at this point to what extent the emotional impact of concussion reflects the physiologic impact of situational/physical/emotional stressors associated with the injury or direct physiologic impact of the injury to the emotional circuitry in the brain ( X. Wang et al, 2017 ). It is also unclear to what extent circuitry associated with resilience, such as pain resilience might also be compromised ( Leung et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important top-down emotion regulation strategies is cognitive reappraisal, which refers to the process of rethinking negative thoughts and changing them into more neutral or perhaps even positive thoughts [58]. Top-down emotion regulation is mainly conducted using the executive network, a network that is also important for cognitive performance [17,57,59]. Neural networks that play a pivotal role in emotion regulation are depicted in Fig.…”
Section: Neural Network and Emotion Regulationmentioning
confidence: 99%
“…To our best knowledge, only two studies have been published that used emotion regulation fMRI paradigms in mTBI. One study demonstrated lower activity in the orbitofrontal cortex and superior parietal lobe during bottom-up emotion induction (i.e., condition in which subjects had to judge whether an angry, fearful or neutral face belonged to a male or female), possibly indicating impaired emotion regulation [59]. These findings were related to higher post-traumatic stress scores.…”
Section: Neural Network and Emotion Regulationmentioning
confidence: 99%
“…SEAT : Left superior parietal gyrus and left medial orbitofrontal gyrus, and lateral orbitofrontal gyri bilaterally (Wang et al, 2017)…”
Section: Discussionmentioning
confidence: 99%
“…Most of the recent studies have used working memory tasks (N‐back) for their ease of presentation in the scanner as well as for their sensitivity to alterations in brain activity. Other tasks proven to be useful in studies on the role of fMRI in the diagnosis of mTBI are, among others, the spatial navigation task (Holmes et al, 2019; Saluja et al, 2015), the Flanker task (Sullivan, Hayes, Lafleche, Salat, & Verfaellie, 2018), the Shifted‐attention Emotion Appraisal Task (SEAT; Wang et al, 2017) and the visual tracking eye movement tests (Astafiev et al, 2015).…”
Section: Methodsmentioning
confidence: 99%